DETERMINING FACTOR FOR MALAYSIAN MONEY DEMAND FUNCTION - Muhammad Ahmad Mazher; Jauhari Dahlan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The reason for our study was to determine the factors that influence the role of money demand in the Malaysian economy. We implicit various economic factors comprise real CPI, real interest rate, financial innovation, and real GDP and analyzed through implying ARDL Bound test for short-run and the long-run period over 1970-2018 time-series data. Based on empirical results, we revealed that over the short-run period, financial innovation having positive and significant while real GDP has a negative and significant relationship with real money demand function in Malaysia. The official real exchange rate has a positive and significant relationship with real money demand, with an increase of one unit in the real exchange rate, increasing the money demand function by 0.97 in the long term. More, negative and significant relationships revealed among real GDP and real money demand function which direct that by increase 1% change in real GDP direct to decrease in real money demand by 0.6395 in the Malaysian economy and finally real money demand predicted 13.0796 when all independent variable is zero in the Malaysian economy.